Fire and memory : on architecture and energy - Fernández-Galiano, Luis (MIT Press, 2000)
Galiano points out that energy, so important to the origins of architectural theory in Vitruvius's time, has been absent from such theory since the introduction of the "dictatorship of the eye" over the other senses. With Fire and Memory, he reintroduces energy to the discussion of architecture and reminds us that the sense of touch is as necessary to an understanding of the environment as the sense of sight."--Jacket.
Keywords: Architecture and energy conservation.; Solar buildings.; Symbolism in architecture.; Architecture et économies d'énergie.; Constructions solaires.; Symbolisme en architecture.; energy efficient buildings.; solar buildings.; ARCHITECTURE -- Sustainability & Green Design.; Architecture and energy conservation; Solar buildings; Symbolism in architecture; Energiebewusstes Bauen; Art, Architecture & Applied Arts.; Architecture.; v -- Writings.